iDrink company / Muhammad Adam Shahairul Rizwan ... [et al.] - Shahairul Rizwan, Muhammad Adam; Mohd Yassin, ‘Nurul Aliah; Norhisham, Muhammad Danish Ammar; Suliman, Siti Nuraini; Madsiam, Nurazieyana; Juhari, Joeaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
How can water bottles be made better for people with disabilities? People with disabilities often find it hard to stay hydrated because they might struggle to hold or use regular water bottles such as to move their hands well or move around. According to this problem, we introduce a new type of water bottle that solves these problems. The design features focus on how people with disabilities drink, how to open the water bottle and making it easier for them to hold or bring it anywhere. So, the iDrink Company chose to help overcome challenges they face which is great for people who use wheelchairs or have difficulty gripping. The idea of designing products is attractive to everyone use it for daily use. Different ages of older people, children and individuals recovering from injuries can increase our potential reach in the market. By listening to users and working together, this product can show the positive impact of considering everyone’s needs and creating a more understanding because it can be used by a wide range of people.